Economic-Political Orientations and Perceptions of The Riau Community: Social Embeddedness, Political Efficacy, and Islamic Financial Inclusion - Eka Armas Pailis; Azhari Setiawan; M. Hamid; Darmayuda Darmayuda; M. Hasnan (AIBPM Publisher, 2025)
Civic engagement and political efficacy as non-economic factors do have significant impact on sharia economy inclusion agenda in Riau Province. Existing literatures found that Islamic economic principles have significant impact on banking and finance sectors which have been felt by us nowadays along with its impact on investment and capital markets, labor market, taxation system, and economic behavior. But it is still underdiscussed when it comes to some inquiries on to what extent non-economic factors contribute to this agenda. Drawing from our public survey data on 911 respondents which is distributed proportionally in each district in Riau Province, we found that besides education level in term of modernization theory, religiosity, civic engagement, and political efficacy have significant effects on sharia economic and finance inclusion. Using multiple regression and ANOVA technique, our study shows that political attitudes and voting for Islamic parties also determine the rate of sharia economy index in Riau context. Regarding these political factors, we also found that criticism of people’s views on government’s works and programs could positively drive the participation and literacy on sharia economy and finance.